Taxonomic status of the Lesser Woolly Horseshoe bats (Chiroptera, Rhinolophidae, Rhinolophus beddomei) in peninsular India and Sri Lanka - Srinivasulu, Aditya; Srinivasulu, Bhargavi; Kusuminda, Tharaka; Amarasinghe, Chamara; Ukuwela, Kanishka D. B.; Karunarathna, Mathisha; Mannakkara, Amani; Yapa, Wipula B.; Srinivasulu, Chelmala (Zootaxa, 2023)
Insularity provides ample opportunities for species diversification. Sri Lanka is home to a large diversity of species, many of which are endemic but morphologically similar to species found in southern India, due to recent speciation events, suggesting a complex evolutionary history. However, in some taxa although morphological diversity has been noted, the genetic level variations are minimal. Among the wide-ranging horseshoe bats such a phenomenon is noted. In this study, we used bioacoustics, morphometric and molecular data to evaluate the relationships between the taxa of lesser woolly horseshoe bats in the India and Sri Lanka. Our study reveals that the two taxa—Rhinolophus beddomei Andersen, 1905 and here we have validated the existing subspecies from peninsular India and R. sobrinus Andersen, 1918 from Sri Lanka are genetically very close to R. perniger Hodgson, 1843. Currently the taxa—beddomei and sobrinus are recognized as subspecies of Rhinolophus beddomei Andersen, 1905. We provide a detailed description of the taxa beddomei and sobrinus as the original descriptions are limited in nature.